The Analysis of Wages and Social Security Not Provided to Workers in View of the Employment Law - Rioneldi, Rizky; Mahmudah, Siti (Jurnal Daulat Hukum, 2023)
The provisions of Article 54 paragraph (1) of Law Number 13 of 2003 concerning Employment emphasize that those who have reached an agreement with employers have rights and obligations that must be carried out. Workers are obliged to carry out the tasks that must be completed so that they are entitled to receive wages from their work. At the same time, employers are obliged to pay wages to obtain the right to work from workers, meaning that employers must not pay wages arbitrarily or late. The purpose of this research is to determine and analyze the legal protection and company accountability for workers whose wages and social security are not provided in terms of the Employment and Accountability Law. This research uses a normative juridical research type, with data collection methods using library methods. The legal material analysis method used in this research uses a qualitative analysis method. The results of his research concluded that wages are an important and fundamental part of employment-management relations, so that the "Employment Law" and government regulation 78/2015 provide protection for wages and social security. The heaviest sanction for a company is in the form of revocation of its business license, because the company cannot be held responsible at all.